The Profile of Creative Thinking Skills of Junior High School Students in Science Learning About Alternative Energy - Fitri Amaliyah; Supeno Supeno; Sri Wahyuni (Universitas Pendidikan Mandalika, 2023)
This research aims to explore junior high school students' creative thinking skill profile in science learning about alternative energy. This research was a quantitative descriptive essay test method. Respondents were 128 7th-grade junior high school students in Jember, East Java, Indonesia. The essay test consists of eight open-ended questions. Every indicator of creative thinking skill consists of two questions number. The Test score would be analyzed by IBM SPSS Statistic 23 using descriptive analyses, frequency analyses, one-sample Kolmogorov-Smirnov tests, validity tests by Pearson correlation, reliability tests, linearity tests, and regression analyses. The results showed that the creative thinking skills of junior high school students were unsatisfactory. Creative thinking skills still need improvement in science learning. Some students had challenges finding and designing a unique creative work on alternative energy. The results of this study implied that creative thinking skills must improve by developing learning methods, strategies, activities, approaches, media, context, and interaction in the discussion process.